Theory of knowledge: a comparative epistemological study of Islamic and western thinkers in developing economic theories - Shaharizan, Lydia Sorfina; Akbar, Mohamed Aslam (AID Conference, 2021)
Knowledge is the most important and powerful tool for any civilization as people with knowledge can observe the world at a higher level than people without knowledge. Knowledge is generally defined as understanding something. In generating knowledge, intellect, which was given to almost all human beings, is needed especially in a highly developed civilization to get new information, ideas, or knowledge about nature, life as well as their way of life. Therefore, the theory of knowledge has always been in discussion as the process of human thinking is difficult to dissect. Many scholars had tried to give their idea on the theory of knowledge where some are still in use while some are lost. This paper reviews the contribution of both Muslim and western scholars in the theory of knowledge and offers a comparative epistemological study to explore the impact that led to developing theories of their time. Three Muslim scholars namely al-Ghazali and al-Shatibi and Ibn Khaldun, and three western scholars namely Adam Smith, John Stuart Mill, and John Maynard Keynes and their opinions are analyzed to emphasize how their worldviews had given an impact on the field of economics and to what extend people in this contemporary world have applied these scholars’ ideas in their personal and public life.